Inspire Challenge Award: Farm.ink: Analysing livestock social media data for farmer chatbot - CGIAR Platform for Big Data in Agriculture (2018)
Grew its user base from around 30,000 at launch to over 120,000 farmers, enabling animal health researchers to reach 24,000 dairy farmers. A recent survey of over 400 dairy chatbot users showed 92% improved their farming practices as a result of what they learned through the service.